2018
DOI: 10.3390/ijms19102999
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sarcopenia as a Prognostic Biomarker of Bladder Cancer

Abstract: Sarcopenia, the degenerative and systemic loss of skeletal muscle mass, indicates patient frailty and impaired physical function. Sarcopenia can be caused by multiple factors, including advanced age, lack of exercise, poor nutritional status, inflammatory diseases, endocrine diseases, and malignancies. In patients with cancer cachexia, anorexia, poor nutrition and systemic inflammation make the metabolic state more catabolic, resulting in sarcopenia. Thus, sarcopenia is considered as one of manifestations of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 75 publications
2
31
0
Order By: Relevance
“…Sarcopenia in the elderly is often related to adverse health outcomes including a higher risk of hospitalization and mortality with associated increased healthcare costs [7,8]. Recently, sarcopenia was implicated as a prognostic factor in a wide range of diseases, such as cancer [9,10], chronic liver diseases [11], chronic pancreatitis [12], rheumatic diseases [13] and inflammatory bowel disease (IBD) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia in the elderly is often related to adverse health outcomes including a higher risk of hospitalization and mortality with associated increased healthcare costs [7,8]. Recently, sarcopenia was implicated as a prognostic factor in a wide range of diseases, such as cancer [9,10], chronic liver diseases [11], chronic pancreatitis [12], rheumatic diseases [13] and inflammatory bowel disease (IBD) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sarcopenia can contribute to higher rates of treatment-related complications in various cancers, including those due to surgical treatment, chemotherapy, or tyrosine kinase inhibitors [25,26,27]. As for urothelial carcinoma, many studies reported that sarcopenia was significantly associated with higher rates of treatment-related complications and worse prognosis [28]. Sarcopenia was a significant predictor for higher rates of perioperative complications and worse cancer-specific survival after radical cystectomy [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we were unable to reveal the mechanism underlying the relationship between a low PMI and a poor prognosis in penile cancer. A low PMI has been thought to reflect anemia, a low BMI, inadequate nutrition, and the effects of other diseases [22]. Thought this findings, the molecular mechanism has yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%